ANALYSIS OF THE RESULTS OF SURGICAL TREATMENT OF LOCALLY ADVANCED GASTRIC CANCER - Khamidov M.; Khasanov D. S. (Scholars Digest Publishing, 2024)
Currently, aggressive surgical tactics are becoming more and more distinct, the proponents of which advocate the most complete removal of a stomach tumor in a locally widespread process. However, this approach is not shared by all surgeons. Indications for combined resections and palliative interventions remain contradictory.
Keywords: locally advanced cancer of the distal stomach, surgical treatment, long-term results.